2009
DOI: 10.1213/ane.0b013e3181b5a234
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Electroacupuncture on Th1/Th2 Cytokine mRNA Expression and Mitogen-Activated Protein Kinase Signaling Pathways in the Splenic T Cells of Traumatized Rats

Abstract: EA regulates a balance between Th1 and Th2 cytokines at protein and mRNA levels in splenic T cells, and, at least in part, involves the signaling pathways of ERK1/2, p38, NF-kappaB, and AP-1. The findings suggest that EA may improve immune suppression after surgical trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 27 publications
4
40
1
Order By: Relevance
“…In our previous study, surgical trauma was associated with decreased expression levels of IL-2 and IFN-γ, increased expression levels of IL-4 and IL-10, and immunosuppression in a surgical trauma rat model (27). In the present study, the expression levels of Th 17 -associated cytokines in patients with lung cancer were decreased following thoracotomy, which may have promoted an imbalance in numbers of Th 1 , Th 2 , Th 17 and T reg cells, and contributed to postoperative immunosuppression.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous study, surgical trauma was associated with decreased expression levels of IL-2 and IFN-γ, increased expression levels of IL-4 and IL-10, and immunosuppression in a surgical trauma rat model (27). In the present study, the expression levels of Th 17 -associated cytokines in patients with lung cancer were decreased following thoracotomy, which may have promoted an imbalance in numbers of Th 1 , Th 2 , Th 17 and T reg cells, and contributed to postoperative immunosuppression.…”
Section: Discussionmentioning
confidence: 86%
“…17 Cheng et al 18 noted that EA at ST36 acupuncture point might increase lymphocyte proliferation of surgically traumatised rats. 8 These results also suggested that acupuncture might improve immunosuppression after surgical trauma. A comparison with previous studies indicated that a similar effect of EA was also observed during craniotomy.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies [12,13,14] and our experiment [15] demonstrated that the surgical trauma model of rats can imitate clinical features, and was used to illustrate the effects of surgical trauma and stress on the body function, and this model was relatively easy to perform. Surgical trauma and anesthesia were performed by two researchers who were not involved in data acquisition and analysis.…”
Section: Methodsmentioning
confidence: 91%